THE COMPLEXITY OF REGULATING INDEPENDENT REGIONAL HEAD CANDIDATES IN ACEH - Muhammad Yus, Sulthan; Muhammad Ridwansyah (Jurnal Hukum Samudra Keadilan, 2024)
This article wishes to highlight that the arrangement of individual candidates has been given space by Law Number 11 of 2006 concerning Aceh Governance. The issue of this gift is that after the conflict, several GAM combatants expressed their desire to advance as regional heads in Aceh; this has also been seen in the draft of the Helsinki MoU. GAM will nominate representatives to participate fully in politics in Aceh after the formation of local political parties. So, on the basis of this construction, individual candidates are adopted in Article 67, paragraph (1), of Law Number 11 of 2006. But on the other hand, individual candidates are also allowed in other regions even though the percentage is different. Article 41, paragraph (1), of Law Number 10 of 2016. The two regulations regarding individual candidates in the laws and regulations in Indonesia overlap if implemented in Aceh. There should be a simulation of the two arrangements so that the KIP Aceh district/city technical level is not mistaken.